IMPLEMENTASI STRATEGI KOMISI PEMILIHAN UMUM KABUPATEN BANDUNG TERKAIT PENINGKATAN PARTISIPASI PEREMPUAN DALAM KONTESTASI POLITIK PADA PEMILIHAN UMUM 2024 - Ilham Fauziasyah; Rendy Adiwilaga (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2024)
The diversity of society which makes Indonesia rich in differences is an important basis for being democratic. This is a strong basis for gender equality in holding control of government, therefore women have rights in the political realm, as this is mandated by Law Number 7 of 2017 article 173 paragraph (2) concerning political parties. This research aims to analyze and determine the implementation of the Bandung Regency General Election Commission (KPU) strategy regarding increasing women's participation in political contestation in the 2024 elections. The research method used is a qualitative research method with a narrative approach, and data was collected through in-depth interviews with several members. Bandung Regency commissioner and female legislative candidate nominated by a political party. The research results show that the implementation of the Bandung Regency General Election Commission (KPU) strategy regarding increasing women's participation in political contestation in the 2024 election is considered less than optimal. So far what the Bandung Regency KPU has carried out is only supervision. The Bandung Regency KPU is hampered in implementing the program due to a lack of human resources and the budget spent is less effective and efficient. However, in carrying out the Regency KPU procedures, it is in accordance with PKPU regulations Number 10 of 2023 concerning Nomination of Members of the DPR, Provincial DPRD, Regency/City DPRD.